Presentation of a Causal Model of Academic Engagement Based on School Climate, Epistemological Beliefs, and Problem-Solving Styles with the Mediating Role of Academic Self-Efficacy - Akbari, Faezeh; Zarnaghash, Maryam; Sohrabi, Nadereh; Barzegar, Majid (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to present a causal model of academic engagement based on school climate, epistemological beliefs, and problem-solving styles, with the mediating role of academic self-efficacy.Methods and Materials: This study was of a correlational type and employed the structural equation modeling (SEM) method. The statistical population included all high school students in Bushehr County during the 2022-2023 academic year, totaling 1,350 individuals. Based on Cochran's formula, a sample of 299 students was selected through cluster random sampling. Data were collected using the Academic Engagement Questionnaire by Reeve, the School Climate Questionnaire, the Epistemological Beliefs Questionnaire by Schommer, the Problem-Solving Styles Questionnaire by Cassidy and Long, and the Academic Self-Efficacy Questionnaire by Jinks and Morgan. Data analysis was conducted using Pearson correlation, regression analysis, and path analysis methods.Findings:  The research findings indicated that school climate has a direct effect on academic self-efficacy. Epistemological beliefs have a direct effect on academic self-efficacy. Constructive problem-solving styles do not have a significant effect on academic self-efficacy in high school students. Non-constructive problem-solving styles have a significant positive effect on academic self-efficacy in high school students. Academic self-efficacy has a direct effect on academic engagement. School climate has a direct effect on academic engagement. Epistemological beliefs have a direct effect on academic engagement. Constructive problem-solving styles have a significant effect on academic engagement in high school students. Non-constructive problem-solving styles do not have a significant positive effect on academic engagement in high school students. School climate indirectly affects academic engagement through the mediating role of academic self-efficacy. Epistemological beliefs indirectly affect academic engagement through the mediating role of academic self-efficacy. Constructive problem-solving styles do not have an indirect effect on academic engagement considering the mediating role of academic self-efficacy. Non-constructive problem-solving styles have an indirect effect on academic engagement considering the mediating role of academic self-efficacy.Conclusion: The study confirms that school climate, epistemological beliefs, and problem-solving styles significantly influence academic engagement, with academic self-efficacy playing a critical mediating role. These findings highlight the importance of fostering a positive school environment and developing students' self-efficacy and epistemological beliefs to enhance academic engagement and performance.